Preparation method and application of thickening double cross-linking adhesive
By using thickened double crosslinking adhesive in coating printing, the problem of difficulty in achieving bonding, thickening and soft effects in the prior art is solved, and the effect of high color fastness, good feel and simplified printing process is achieved.
Patent Information
- Application Number
- CN202310023907.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-09
AI Technical Summary
The prior art is difficult to achieve the bonding, thickening and softening effects simultaneously in paint printing, resulting in the thick and hard feel of the printed fabric and insufficient color fastness.
Thickable double crosslinking adhesive is used, which consists of components A and components B. When preparing color paste, the cross-linking effect of component A and component B provides a thickening effect, optimizing the color paste preparation process; when baking printed fabrics, component A and cotton fabrics cross-link to form a film to improve color fastness; component B serves as a softener to improve the feel of the fabric.
It has achieved simplified the color paste preparation process in paint printing, improved the color fastness and consumption performance of printed fabrics, and improved the feel of the fabric.
Smart Images

Figure CN116043581B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of adhesive synthesis, and in particular to a preparation method of a thickening double-crosslinking adhesive and its application. Background Art
[0002] Pigment printing has the advantages of complete color spectrum, bright colors, easy color matching, etc., and can be applied to all types of fabrics. It is a more commonly used printing method. Since the paint has no binding force on the fiber, it is usually necessary to add an adhesive to form a film to adhere the pigment to the surface of the fabric to ensure the color fastness of the printed fabric.
[0003] The quality and performance of pigment-printed fabrics depend largely on the performance of the adhesive. At present, water-based polyacrylate adhesives are widely used in the printing industry. This is because polyacrylate adhesives are easy to prepare and can be quickly dried and solidified. However, this type of adhesive has the defects of being hot and viscous and cold and brittle, and often affects the feel of printed fabrics; polyurethane is a block copolymer. The flexible segments in the molecule give it good flexibility, while the rigid segments give it good mechanical properties. By utilizing the high reactivity of the isocyanate group of polyurethane to react with the active group, a reactive polyurethane adhesive can be obtained, which reduces the loss of fabric feel while improving color fastness. The cross-linking agent can react with the adhesive or the fabric, and by enhancing the degree of cross-linking, various color fastness can be further improved.
[0004] Thickeners need to be added to printing pastes to ensure the rheological properties of the pastes and weaken the effect of the permeation caused by the capillary action of the fabric on the clarity of the print. Traditional polyacrylic thickeners have good thickening properties, but the printed fabric feels rough and hard; in addition, the higher baking temperature will affect the wearing properties of cotton fabrics. It is a novel idea to prepare a two-component adhesive that has bonding, thickening and softening effects, which simplifies the preparation process of printing pastes while ensuring the fastness of printed fabrics and increasing the added value of printed products. Most of the polyurethanes prepared at present cannot achieve this. The Chinese invention patent application with application number CN202110574158.X (publication number CN113462343A) discloses a two-component water-based polyurethane adhesive and a preparation method thereof. The polyurethane adhesive has good bonding properties and certain water resistance, and can be used in high-humidity environments; the Chinese invention patent application with application number CN201610047858.2 (publication number CN105669942A) discloses a polyurethane modified paint printing adhesive. The adhesive has good viscosity, and when applied to paint printing, the printed fabric has good color performance and hand quality; in 2016, Yang Huazhang, a student of textile chemistry and dyeing and finishing engineering at Xi'an Polytechnic University, disclosed an article entitled "Preparation and Modification of Water-Based Polyurethane for Paint Printing", which used self-made polyester-polyether polyurethane and modified polyurethane as adhesives, and blocked polyurethane as a cross-linking agent, which were applied to paint printing of cotton fabrics and polyester-cotton fabrics, which can give the fabric a good hand feel while ensuring color fastness.
[0005] The above polyurethane adhesives all have good adhesive properties and meet the fastness requirements of the product. Some polyurethane adhesives can also give the printed products a good feel. However, in the process of color paste preparation, thickeners need to be added to give the color paste rheology, and they cannot be directly used in the preparation of color paste. Summary of the invention
[0006] The purpose of the invention is to provide a method for preparing a thickening double cross-linking adhesive and to apply the method to pigment printing of cotton fabrics.
[0007] In order to achieve the above objectives, this application mainly provides the following technical solutions:
[0008] A thickening double cross-linking adhesive is composed of component A and component B. When preparing the color paste, it can have a thickening effect, optimizing the color paste preparation process; when the printed fabric is baked, the cross-linking effect of component A with the cotton fabric and component B ensures the color fastness of the printed fabric; in addition, component B acts as a softener, giving the printed fabric a good hand feel. Increasing the pre-baking temperature promotes the deblocking of the methyl ethyl ketone oxime-terminated -NCO and accelerates the loss of moisture, simplifying the printing process.
[0009] A method for preparing a thickening double cross-linking adhesive comprises dispersing component A and component B in water, stirring, and then concentrating by rotary evaporation; wherein the preparation process of component A is as follows:
[0010] (1) dispersing diisocyanate, polyethylene glycol and a catalyst as raw materials in an organic solvent, mixing and performing a prepolymerization reaction to obtain a waterborne polyurethane prepolymer;
[0011] (2) then adding a chain extender to continue the chain extension reaction;
[0012] (3) After the chain extension reaction is completed, the temperature is lowered and a capping agent is added to carry out a capping reaction;
[0013] (4) After the end-capping reaction is completed, the temperature is lowered, and a neutralizing agent is added to carry out a neutralization reaction to obtain component A;
[0014] The preparation process of the B component is:
[0015] (1) dispersing diisocyanate, branched structure monomer, and catalyst as raw materials in an organic solvent, mixing and performing prepolymerization reaction to obtain a polyurethane prepolymer;
[0016] (2) then cooling and adding a capping agent to carry out a capping reaction;
[0017] (3) After the end-capping reaction is completed, the temperature is raised, and a long-chain fatty acid is added to carry out a ring-opening reaction under catalyst conditions to obtain a hydrophobic segment with a branched structure;
[0018] (4) dispersing diisocyanate, polyethylene glycol and catalyst as raw materials in an organic solvent and mixing them for prepolymerization;
[0019] (5) After the reaction is completed, the temperature is maintained constant and the hydrophobic segment with a branched structure obtained in step (3) is added to carry out a capping reaction to obtain component B.
[0020] Preferably, in the preparation process of component A, the diisocyanate is one of isophorone diisocyanate and hexamethylene diisocyanate; the polyethylene glycol is one of PEG400, PEG600 and PEG1000; the catalyst is dibutyltin dilaurate; the organic solvent is one of acetone or butanone; the chain extender is one of 2,2-dihydroxymethylpropionic acid or 2,2-dihydroxymethylbutyric acid; the capping agent is one or both of propylene oxide or methyl ethyl ketone oxime; and the neutralizing agent is triethylamine.
[0021] Preferably, during the preparation of component A, the molar ratio of diisocyanate to polyethylene glycol is 4:(1-1.2).
[0022] Preferably, during the preparation of component A, the molar ratio of diisocyanate to catalyst is 4:(0.07-0.09).
[0023] Preferably, during the preparation of component A, the molar ratio of diisocyanate to chain extender is 4:(0.3-2).
[0024] Preferably, during the preparation of component A, the molar ratio of diisocyanate to blocking agent is 4:(2-5).
[0025] Preferably, during the preparation of component A, the molar ratio of diisocyanate to neutralizer is 4:(0.4-0.6).
[0026] Preferably, in the preparation process of component A, the reaction temperature in step (1) is 65-75°C and the reaction time is 2-2.5h; the reaction time in step (2) is 2-2.5h; the reaction temperature in step (3) is 50-65°C and the reaction time is 2-2.5h; the reaction temperature in step (4) is 30-40°C and the reaction time is 0.5-1h.
[0027] Preferably, in the preparation process of component A, the amount of the organic solvent used in step (1) is 50 ml to 100 ml.
[0028] Preferably, in the preparation process of component B, the diisocyanate in step (1) is one of isophorone diisocyanate and hexamethylene diisocyanate, the branched structure monomer is one of trimethylolpropane, trimethylolaminomethane, and pentaerythritol, the catalyst is dibutyltin dilaurate, and the organic solvent is N,N-dimethylformamide; the capping agent in step (2) is propylene oxide; the long-chain fatty acid in step (3) is one of palmitic acid and stearic acid, and the catalyst is triphenylphosphine.
[0029] Preferably, in the preparation process of component B, in steps (1) to (3), the molar ratio of the diisocyanate to the branched structural unit is (3-4):1.
[0030] Preferably, in the preparation process of component B, in steps (1) to (3), the molar ratio of dibutyltin dilaurate to the branched structural unit is (0.07-0.09):1.
[0031] Preferably, in the preparation process of component B, in steps (1) to (3), the molar ratio of the end-capping agent to the branched structural unit is (3-4):1.
[0032] Preferably, in the preparation process of component B, in steps (1) to (3), the molar ratio of triphenylphosphine to branched structural unit is (0.1-0.2):1.
[0033] Preferably, in the preparation process of component B, in steps (1) to (3), the molar ratio of the long-chain fatty acid to the branched structural unit is (3-4):1.
[0034] Preferably, in the preparation process of component B, in steps (4) to (5), the molar ratio of the diisocyanate to the polyethylene glycol is (4-6):1.
[0035] Preferably, in the preparation process of component B, in steps (4) to (5), the molar ratio of the catalyst to polyethylene glycol is (0.07-0.09):1.
[0036] Preferably, in the preparation process of component B, in steps (4) to (5), the molar ratio of the hydrophobic segment having a branched structure to the polyethylene glycol is (3-4):1.
[0037] Preferably, in the preparation process of component B, the diisocyanate in step (4) is one of isophorone diisocyanate and hexamethylene diisocyanate, the polyethylene glycol is one of PEG2000, PEG4000 and PEG6000, the catalyst is dibutyltin dilaurate, and the organic solvent is one of acetone, butanone, and N,N-dimethylformamide.
[0038] Preferably, in the preparation process of component B, the reaction temperature in step (1) is 65-75°C, and the reaction time is 2-2.5 hours; the reaction temperature in step (2) is 55-65°C, and the reaction time is 2-2.5 hours; the reaction temperature in step (3) is 100-120°C, and the reaction time is 5-9 hours; the reaction temperature in step (4) is 65-75°C, and the reaction time is 2-2.5 hours; the reaction temperature in step (5) is 65-75°C, and the reaction time is 2-2.5 hours.
[0039] Preferably, in the preparation process of component B, the amount of organic solvent used in steps (1) and (4) is 50 ml to 100 ml.
[0040] Preferably, in the thickenable dual cross-linking adhesive, the content of component A is 10%-20%, and the content of component B is 5%-15%.
[0041] Preferably, the application of the prepared thickening double cross-linking adhesive in pigment printing of cotton fabric comprises the following steps:
[0042] In the printing paste, the content of the thickening double cross-linking adhesive is 15%-35%, the content of the coating is 1%, and the printed fabric is pre-baked at 110-130°C for 2-5 minutes and baked at 140-160°C for 3-5 minutes.
[0043] Beneficial effects achieved by the present invention:
[0044] (1) The thickening double-crosslinking adhesive prepared by the present invention can have thickening performance when preparing color paste, thereby achieving the purpose of simplifying the process of preparing pigment printing color paste.
[0045] (2) During the pre-baking and baking processes, component A can undergo cross-linking reactions with component B and cotton fabric respectively, forming a thin film that covers the coating on the surface of the cotton fabric; the dual active groups of component A provide the possibility of dual cross-linking reactions, further improving the printing fastness of the fabric; the higher pre-baking temperature promotes the deblocking of the -NCO capped by methyl ethyl ketone oxime while accelerating the loss of moisture, simplifying the printing process.
[0046] (3) The prepared thickening double-crosslinking adhesive can give cotton fabrics good wearing properties, making up for the loss of flexibility caused by high-temperature baking. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The rheological properties of the color pastes of Examples 1-6 of the present application (a)-f)) are respectively Example 1, Example 2, Example 3, Example 4, Example 5, Example 6);
[0048] Figure 2 The following are actual pictures of the lining cloths used for testing the dry and wet rubbing fastness of printed fabrics (from left to right: Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1, Comparative Example 2, Comparative Example 3). DETAILED DESCRIPTION
[0049] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings and embodiments.
[0050] Isophorone diisocyanate (IPDI), triphenylphosphine (PPh3), analytical grade, Shanghai Titan Technology Co., Ltd.; dimethylolbutyric acid (DMBA), trimethylolpropane (TMP), methyl ethyl ketone oxime (MKEO), analytical grade, Aladdin Reagent Co., Ltd.; glycidol (GLD), polyethylene glycol 6000 (PEG6000), analytical grade, Beijing Inokai Technology Co., Ltd.; polyethylene glycol 600 (PEG600), dibutyltin dilaurate (DBTDL), triethylamine (TEA), acetone, analytical grade, Sinopharm Chemical Reagent Co., Ltd.; stearic acid, analytical grade, J&K Reagent Company; pigment, industrial grade, Shanghai Silian; synthetic thickener: industrial grade, Yimei Chemical.
[0051] Example 1
[0052] (1) Synthesis of component A
[0053] 0.04 mol of isophorone diisocyanate, 0.01 mol of polyethylene glycol 600 and 0.4 g of dibutyltin dilaurate were added to a three-necked flask, and the temperature was raised to 70°C for prepolymerization for 2 hours to synthesize a waterborne polyurethane prepolymer; 0.005 mol of 2,2-dihydroxymethylbutyric acid was added for chain extension reaction at 70°C for 2 hours; the temperature was lowered to 60°C, 0.05 mol of glycidol was added for end-capping reaction for 2 hours; the temperature was lowered to 40°C, 0.005 mol of triethylamine was added for neutralization reaction for 0.5 hours, and 75 ml of acetone was added during the reaction to adjust the viscosity of the system to prepare component A.
[0054] (2) Synthesis of hydrophobic segments with branched structures
[0055] 0.03 mol of isophorone diisocyanate, 0.01 mol of trimethylolpropane and 0.4 g of dibutyltin dilaurate were added to a three-necked flask, and the temperature was raised to 70°C for prepolymerization for 2 hours to synthesize a polyurethane prepolymer; the temperature was raised to 110°C, 0.03 mol of stearic acid and 0.4 g of triphenylphosphine were added and reacted for 9 hours, and 75 ml of N,N-dimethylformamide was added during the reaction to adjust the viscosity of the system to prepare a hydrophobic fragment with a branched structure.
[0056] (3) Synthesis of component B
[0057] 0.005 mol of isophorone diisocyanate, 0.001 mol of polyethylene glycol 6000 and 0.4 g of dibutyltin dilaurate were added to a three-necked flask, and the temperature was raised to 70° C. for prepolymerization for 2 hours to synthesize a polyurethane prepolymer; 0.0036 mol of the hydrophobic segment with a branched structure prepared in Example 1 was added and chain extension reaction was carried out at 70° C. for 2 hours. During the reaction, 75 ml of acetone was added to adjust the viscosity of the system.
[0058] (4) Application of thickening double cross-linking adhesive in pigment printing of cotton fabrics
[0059] Component A and component B are dispersed in water by mechanical stirring, and then vacuum rotated to remove residual organic solvent. The vacuum degree of rotary evaporation is 1Mpa and the temperature is 100℃. Then, the polyurethane aqueous solution is used to prepare the printing paste, in which the content of component A is 15%, component B is 10%, and the coating is 1%. The printed fabric is dried at 120℃ and baked at 150℃ for 3 minutes.
[0060] Example 2
[0061] The synthesis of component A, the hydrophobic segment with a branched structure and component B is the same as in Example 1. The application of the thickening double cross-linking adhesive in the pigment printing of cotton fabric is as follows:
[0062] Component A and component B are dispersed in water by mechanical stirring, and then vacuum rotated to remove residual organic solvent. The vacuum degree of rotary evaporation is 1Mpa and the temperature is 100℃. Then, the polyurethane aqueous solution is used to prepare printing paste, in which the content of component A is 12.5%, component B is 12.5%, and the coating is 1%. The printed fabric is dried at 120℃ and baked at 150℃ for 3 minutes.
[0063] Example 3
[0064] The synthesis of the hydrophobic segment with branched structure and component B is the same as in Example 1.
[0065] (1) Synthesis of component A
[0066] 0.04 mol of isophorone diisocyanate, 0.01 mol of polyethylene glycol 600 and 0.4 g of dibutyltin dilaurate were added to a three-necked flask, and the temperature was raised to 70°C for prepolymerization for 2 hours to synthesize a waterborne polyurethane prepolymer; 0.005 mol of 2,2-dihydroxymethylbutyric acid was added for chain extension reaction at 70°C for 2 hours; the temperature was lowered to 50°C, 0.05 mol of methyl ethyl ketone oxime was added for end-capping reaction for 2 hours; the temperature was lowered to 40°C, 0.005 mol of triethylamine was added for neutralization reaction for 0.5 hours, and 75 ml of acetone was added during the reaction to adjust the viscosity of the system to prepare component A.
[0067] (2) Application of thickening double cross-linking adhesive in pigment printing of cotton fabrics
[0068] Component A and component B are dispersed in water by mechanical stirring, and then vacuum rotated to remove residual organic solvent. The vacuum degree of rotary evaporation is 1Mpa and the temperature is 100℃. Then, the polyurethane aqueous solution is used to prepare the printing paste, in which the content of component A is 15%, component B is 10%, and the coating is 1%. The printed fabric is dried at 120℃ and baked at 150℃ for 3 minutes.
[0069] Example 4
[0070] The synthesis of component A is the same as in Example 3, and the synthesis of the hydrophobic segment with a branched structure and component B is the same as in Example 1. The application of the thickening double cross-linking adhesive in the pigment printing of cotton fabric is as follows:
[0071] Component A and component B are dispersed in water by mechanical stirring, and then vacuum rotated to remove residual organic solvent. The vacuum degree of rotary evaporation is 1Mpa and the temperature is 100℃. Then, the polyurethane aqueous solution is used to prepare printing paste, in which the content of component A is 12.5%, component B is 12.5%, and the coating is 1%. The printed fabric is dried at 120℃ and baked at 150℃ for 3 minutes.
[0072] Example 5
[0073] The synthesis of the hydrophobic segment with branched structure and component B is the same as in Example 1.
[0074] (1) Synthesis of component A
[0075] 0.04 mol of isophorone diisocyanate, 0.01 mol of polyethylene glycol 600 and 0.4 g of dibutyltin dilaurate were added to a three-necked flask, and the temperature was raised to 70°C for prepolymerization for 2 hours to synthesize a waterborne polyurethane prepolymer; 0.005 mol of 2,2-dihydroxymethylbutyric acid was added for chain extension reaction at 70°C for 2 hours; the temperature was lowered to 60°C, and 0.025 mol of propylene oxide was added for end-capping reaction for 2 hours; the temperature was lowered to 50°C, and 0.025 mol of methyl ethyl ketone oxime was added for end-capping reaction for 2 hours; the temperature was lowered to 40°C, and 0.005 mol of triethylamine was added for neutralization reaction for 0.5 hours. During the reaction, 75 ml of acetone was added to adjust the viscosity of the system to prepare component A. (2) Application of thickening double cross-linking adhesive in pigment printing of cotton fabrics
[0076] Component A and component B are dispersed in water by mechanical stirring, and then vacuum rotated to remove residual organic solvent. The vacuum degree of rotary evaporation is 1Mpa and the temperature is 100℃. Then, the polyurethane aqueous solution is used to prepare the printing paste, in which the content of component A is 15%, component B is 10%, and the coating is 1%. The printed fabric is dried at 120℃ and baked at 150℃ for 3 minutes.
[0077] Example 6
[0078] The synthesis of component A is the same as in Example 5, and the synthesis of the hydrophobic segment with a branched structure and component B is the same as in Example 1. The application of the thickening double cross-linking adhesive in the pigment printing of cotton fabric is as follows:
[0079] Component A and component B are dispersed in water by mechanical stirring, and then vacuum rotated to remove residual organic solvent. The vacuum degree of rotary evaporation is 1Mpa and the temperature is 100℃. Then, the polyurethane aqueous solution is used to prepare printing paste, in which the content of component A is 12.5%, component B is 12.5%, and the coating is 1%. The printed fabric is dried at 120℃ and baked at 150℃ for 3 minutes.
[0080] Comparative Example 1
[0081] The same component A as in Example 1 was used to prepare the color paste. The component A was mixed with the synthetic thickener and dispersed in water by mechanical stirring, and then vacuum-rotated to remove the residual organic solvent. The vacuum degree of the rotary evaporation was 1 MPa and the temperature was 50°C. Then, a printing color paste was prepared, in which the component A content was 25%, the synthetic thickener content was 1%, and the coating content was 1%. The printed fabric was dried at 120°C and then baked at 150°C for 3 minutes.
[0082] Comparative Example 2
[0083] The same component A as in Example 3 was used to prepare the color paste. The component A was mixed with the synthetic thickener and dispersed in water by mechanical stirring, and then vacuum-rotated to remove the residual organic solvent. The vacuum degree of the rotary evaporation was 1 MPa and the temperature was 50°C. Then, a printing color paste was prepared, in which the component A content was 25%, the synthetic thickener content was 1%, and the coating content was 1%. The printed fabric was dried at 120°C and then baked at 150°C for 3 minutes.
[0084] Comparative Example 3
[0085] The same component A as in Example 5 was used to prepare the color paste. The component A was mixed with the synthetic thickener and dispersed in water by mechanical stirring, and then vacuum-rotated to remove the residual organic solvent. The vacuum degree of the rotary evaporation was 1 MPa and the temperature was 50°C. Then, a printing color paste was prepared, in which the component A content was 25%, the synthetic thickener content was 1%, and the coating content was 1%. The printed fabric was dried at 120°C and then baked at 150°C for 3 minutes.
[0086] The rheological properties of the color paste in the above examples were tested, and the printing fastness and wrinkle recovery angle of the printed fabrics obtained in the above examples and comparative examples were tested according to the following methods.
[0087] Rheological properties:
[0088] Static rheological test: The shear fluid module of Physica MCR301 rheometer was used to test the change of the color paste viscosity with shear rate at 25°C. The shear rate scanning range was 0-1000s -1 Dynamic rheological test: Through the viscoelastic analysis of the color paste, the dynamic frequency scanning module of the Physica MCR301 rheometer was selected to test the relationship between the storage modulus and loss modulus of the color paste and the frequency at 25°C, with a frequency scanning range of 0-100rad / s.
[0089] Printing fastness:
[0090] The rubbing fastness is determined according to GB / T 3920-2008 "Textiles - Tests for Colour Fastness - Colour Fastness to Rubbing". Dry rubbing fastness test: Fix the printed fabric on the rubbing fastness tester so that the warp direction of the rubbing cloth is consistent with the movement direction of the rubbing head. The rubbing head rubs back and forth 10 times along a 100mm long track on the printed fabric, with a vertical pressure of 9N; Wet rubbing fastness test: Replace the tested position of the printed fabric, and use a wet rubbing cloth with a water content of 95-105% to test according to the above method. After the test, dry the wet rubbing cloth at room temperature, and use a gray sample card to assess the rubbing fastness level.
[0091] Wrinkle recovery angle:
[0092] According to the standard GB3819-1997 "Determination of Crease Recovery of Textile Fabrics - Recovery Angle Method", the samples were tested for their warp and weft wrinkle recovery angles in both the quick and slow directions on the YG(B)541D fabric wrinkle elasticity tester. The sum of the warp and weft wrinkle recovery angles was used to represent the wrinkle resistance. Three samples were tested and the average value was taken.
[0093] like Figure 1 It shows that the color paste prepared with thickening double cross-linking adhesive has a certain viscosity. With the increase of shear rate, the viscosity of the color paste first drops sharply and then slowly. When the shear rate exceeds a certain value, the viscosity of the color paste no longer changes with the increase of shear rate, showing the characteristics of shear thinning. They are all pseudoplastic fluids with good rheological properties. When the ratio of the two components is constant and component A is different, the viscosity of the color paste is close; compared with the color pastes of Example 1, Example 3 and Example 5, the color pastes of Example 2, Example 4 and Example 6 have higher viscosity, which shows that under the same adhesive dosage conditions, the increase in the amount of component B is conducive to the increase of the viscosity of the color paste.
[0094] Table 1 Test of color fastness to rubbing of printed fabrics
[0095]
[0096]
[0097] As shown in Table 1, the dry rubbing fastness of the printed fabric using the thickened double-crosslinked adhesive is approximately level 4, and the wet rubbing fastness is approximately level 3, while the dry rubbing fastness of the printed fabric obtained using the traditional printing paste in the comparative example is approximately level 4, and the wet rubbing fastness is approximately level 2, which indicates that the crosslinking effect of the two components is beneficial to the film formation of the adhesive on the surface of the fabric and the coating of the pigment. The use of the thickened double-crosslinked adhesive can further improve the printing fastness while simplifying the preparation process of the printing paste; at the same time, the dry and wet rubbing fastness of the printed fabric obtained using the paste of component A containing a double reactive group are higher than those of the printed fabric obtained using the paste of component A containing only one reactive group.
[0098] Table 2 Wrinkle recovery angle test of printed fabrics
[0099]
[0100] As shown in Table 2, the warp snap recovery angle and slow rebound recovery angle of the printed fabric obtained by using the printing paste of Examples 1-6 are higher than the snap recovery angle and slow rebound recovery angle of the printed fabric obtained by using the traditional printing paste in Comparative Examples 1-3. This indicates that the two components of the thickening double cross-linking adhesive form cross-links with the macromolecules in the amorphous region of the cotton fabric; compared with the traditional adhesive, the thickening double cross-linking adhesive forms a network cross-link of longer flexible chain segments on the fabric, better restricting the relative movement between cotton fibers, thereby achieving an anti-wrinkle effect and improving the wearing performance of the cotton fabric.
[0101] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a thickening double cross-linking adhesive, characterized in that: The preparation process of component A is as follows: (1) dispersing diisocyanate, polyethylene glycol and a catalyst as raw materials in an organic solvent, mixing and performing a prepolymerization reaction to obtain a waterborne polyurethane prepolymer; (2) then adding a chain extender to continue the chain extension reaction; the chain extender is one of 2,2-dimethylol propionic acid or 2,2-dimethylol butyric acid; (3) After the chain extension reaction is completed, the temperature is lowered and a capping agent is added to carry out a capping reaction; the capping agent is one or both of glycidol or methyl ethyl ketone oxime; (4) After the end-capping reaction is completed, the temperature is lowered and a neutralizing agent is added to carry out a neutralization reaction to obtain component A; The preparation process of the B component is: (1) dispersing diisocyanate, branched structure monomer and catalyst as raw materials in an organic solvent, mixing and performing prepolymerization reaction to obtain a polyurethane prepolymer; the branched structure monomer is one of trimethylolpropane, trimethylolaminomethane and pentaerythritol; (2) Then the temperature is lowered and a capping agent is added to carry out a capping reaction; (3) After the end-capping reaction is completed, the temperature is raised, and a long-chain fatty acid is added to carry out a ring-opening reaction under catalyst conditions to obtain a hydrophobic segment with a branched structure; (4) dispersing diisocyanate, polyethylene glycol and catalyst as raw materials in an organic solvent and mixing them for prepolymerization; (5) After the reaction is completed, the temperature is maintained constant and the hydrophobic segment with a branched structure obtained in step (3) is added to carry out a capping reaction to obtain component B.
2. The preparation method according to claim 1, characterized in that: In the preparation process of component A, the diisocyanate is one of isophorone diisocyanate and hexamethylene diisocyanate; the polyethylene glycol is one of PEG400, PEG600 and PEG1000; the catalyst is dibutyltin dilaurate; the organic solvent is one of acetone or butanone; and the neutralizer is triethylamine.
3. The preparation method according to claim 1, characterized in that: In the preparation process of component A, the molar ratio of diisocyanate to polyethylene glycol is 4:(1-1.2); the molar ratio of diisocyanate to catalyst is 4:(0.07-0.09); the molar ratio of diisocyanate to chain extender is 4:(0.3-2); the molar ratio of diisocyanate to end capping agent is 4:(2-5); and the molar ratio of diisocyanate to neutralizing agent is 4:(0.4-0.6).
4. The preparation method according to claim 1, characterized in that In the preparation process of component A, the reaction temperature in step (1) is 65-75°C and the reaction time is 2-2.5 h; the reaction time in step (2) is 2-2.5 h; the reaction temperature in step (3) is 50-65°C and the reaction time is 2-2.5 h; the reaction temperature in step (4) is 30-40°C and the reaction time is 0.5-1 h.
5. The preparation method according to claim 1, characterized in that: In the preparation process of component B, the diisocyanate in step (1) is one of isophorone diisocyanate and hexamethylene diisocyanate, the catalyst is dibutyltin dilaurate, and the organic solvent is N,N-dimethylformamide; the end-capping agent in step (2) is propylene oxide; the long-chain fatty acid in step (3) is one of palmitic acid and stearic acid, and the catalyst is triphenylphosphine; in steps (1) to (3), the molar ratio of dibutyltin dilaurate to the branched structure monomer is (0.07-0.09):1; in steps (1) to (3), the molar ratio of triphenylphosphine to the branched structure monomer is (0.1-0.2):
1.
6. The preparation method according to claim 1, characterized in that: In the preparation process of component B, in steps (1) to (3), the molar ratio of the diisocyanate to the branched structure monomer is (3-4):1; in steps (1) to (3), the molar ratio of the capping agent to the branched structure monomer is (3-4):1; in steps (1) to (3), the molar ratio of the long-chain fatty acid to the branched structure monomer is (3-4):1; in steps (4) to (5), the molar ratio of the diisocyanate to polyethylene glycol is (4-6):1; in steps (4) to (5), the molar ratio of the catalyst to polyethylene glycol is (0.07-0.09):1; in step (5), the molar ratio of the hydrophobic segment with a branched structure to polyethylene glycol is (3-4):
1.
7. The preparation method according to claim 1, characterized in that: In the preparation process of component B, the diisocyanate in step (4) is one of isophorone diisocyanate and hexamethylene diisocyanate, the polyethylene glycol is one of PEG2000, PEG4000 and PEG6000, the catalyst is dibutyltin dilaurate, and the organic solvent is one of acetone, butanone and N,N-dimethylformamide.
8. The preparation method according to claim 1, characterized in that: The content of component A in the thickened double cross-linking adhesive is 10%-20%, and the content of component B is 5%-15%.
9. A thickenable dual cross-linking adhesive prepared by the method according to any one of claims 1 to 8.
10. A printing paste containing the thickenable double cross-linkable binder as claimed in claim 9.
Citation Information
Patent Citations
Polyurethane-modified pigment printing binding agent preparation method
CN105669942A
Two-component waterborne polyurethane adhesive and preparation method thereof
CN113462343A
Cross-linking agent for imitation active pigment printing and preparation method of cross-linking agent
CN107955129A
Preparation method of reactive branched polyurethane polymeric dispersant
CN112778488A